PERLAKUAN AKUNTANSI MURABAHAH DALAM PEMBIAYAAN KPR (KREDIT PERUMAHAN RAKYAT) SYARIAH DITINJAU DARI PSAK NO.102 PADA BANK BTN SYARIAH SURABAYA - NURLATIFAH, AMIRA (Jurnal Akuntansi AKUNESA, 2015)
Abstract: The aim of this study was to determine the application of the murabaha contract in mortgage financing products with type of mortgage financing BTN Platinum iB, either transparency or accounting processes and operational processes must be recorded properly. Results from this study indicate that the implementation of financing by using murabaha contract in mortgage financing products with type of mortgage financing BTN Platinum has not yet fully implemented entirely in accordance with PSAK No. 102 on accounting murabaha terms of recognition and measurement of accounting for repayment and discount murabaha pieces. Conclusion of this study indicate that the accounting treatment of murabaha in mortgage financing products with type of mortgage financing BTN Platinum iB not fully implemented in accordance with PSAK No. 102 on accounting murabaha in Bank BTN Syariah Surabaya. Keywords: PSAK No. 102, Murabaha Accounting, House Financing Credit Sharia, BTN                     Syariah Bank Surabaya